Quality control by furniture manufacture / Mohd Ikram Ibrahim and Muhamad Amin A. Rahaman - Ibrahim, Mohd Ikram; A. Rahaman, Muhamad Amin (2008)
(Tunggu keyword) The process of quality control is the last of a sequence of manufacturing actions, neither more nor less important that all the previous. The application of quality control is it protect the surface and also to enhance the esthetic qualities of timbers. In this process, quality control in machining, quality control in finishing, and quality control in packaging is taking more importance for manufacturing process. In this study, quality control of manufacturing process to improve the product quality.